DETERMINAN KEBIJAKAN DIVIDEN PADA SEKTOR NONKEUANGAN - Pratama, Ahmad Aziz Putra (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2019)
This study aims to determine the effect of company size, leverage, growth opportunities, return on on equity, price earnings ratio, quick ratio and free cash flow on dividend policy in non-financial companies listed on the Indonesia Stock Exchange during the 2013-2018 period. This study uses 122 with a total of 732 observations using purposive sampling method with multiple linear regression models. This study was processed using SPSS 25. The independent variables in this study are size, leverage, growth opportunities, ROE, PER, quick ratio, and free cash flow. The dependent variable in this study is dividend policy. Based on the analysis results, it can be concluded that size and PER have a significant positive effect on dividend policy, quick ratio and free cash flow have a positive and insignificant effect on dividend policy, while leverage and ROE have no significant negative effect on dividend policy, and growth has a significant negative effect on dividend policy.